Breaking Barriers: The Impact of the Affective Filter on English Education Students Speaking Performance in Class - Nyssa Khairina; Amanda Apta Nurjannah Ardhiyanto (Program Studi Magister Tadris Bahasa Inggris UIN Sultan Maulana Hasanuddin Banten, 2025)
This research aims to analyze the influence of affective filters, Krashen’s theory, on students’ speaking performance through the three affective filters: self-confidence, motivation, and anxiety. A qualitative study was used to understand how affective filters influence students’ speaking performance. To collect the data, the researchers used questionnaires distributed to 10 participants of English Education students. The result shows that self-confidence becomes the main factor that makes their speaking ability low. Anxiety can also make it even worse. However, most students are highly motivated to learn English, mainly when speaking English. Therefore, teachers should provide a supportive learning environment to help the students reduce anxiety and enhance self-confidence.